Unpacking the Aesthetics of Working in Public Space in Malaysia and Southeast Asia through the Lens of Art-Led Participative Processes. Issue 4 (2nd September 2020) - Koh, Jay
Abstract: This article examines the organisation and methodologies of current art and cultural collectives in Malaysia, with resonance for Southeast Asia, through the lens of socially engaged and public participatory art theories. The article proposes an inclusive aesthetics that looks at the complementary effects of dialogue, reciprocity, transitional meaning and durational process in responding to the everyday. It employs the framework of Art-Led Participative Processes, a concept - based cross disciplinary critical framework that I have constructed to raise discussion. The works of Buku Jalanan will be mapped out within the contexts of Kuala Lumpur, those of inherited postcolonial structures that prescribes current usage of public spaces, acts of expression and activities, paying attention to a particular form of 'distant subjectivity' that informs contemporary cultural values called 'functional harmony' that is prevalent in Southeast Asia. The experiences of BJ, while not treated as representational of other collectives, are used to launch discursive points for coming to terms with open-structured, socially engaged, public participative and democratic activities.